Factors Associated with Recurrent Ulcers in Patients with Gastric Surgery after More Than 15 Years: A Cross-Sectional Single-Center Study. (4th November 2018) - Pantea, Monica; Negovan, Anca; Banescu, Claudia; Bataga, Simona; Neagoe, Radu; Mocan, Simona; Iancu, Mihaela
Abstract : Aim . We aimed to establish the independent predictive factors (from Helicobacter pylori infection, biliary reflux, histologic features of the gastric mucosa, drugs, comorbidities, and social habits) for gastric stump ulcer occurrence more than 15 years after surgery. Methods . 76 patients with previous gastric surgery were included: 21 patients with gastric ulcer (marginal ulcer or ulcer of the rest of the gastric remnant—study group) and 55 controls (nonulcer group). Results . Helicobacter pylori infection tended to be higher in the control group than in the ulcer group (14.5% vs. 4.8%, p = 0.43 ), without statistical significance. Alcohol consumption had a significant positive association with ulcer (p = 0.008 ), while smoking (p = 0.064 ), low-dose aspirin (p = 0.063 ), and biliary reflux (p = 0.106 ) had a tendency toward statistical signification for positive association. On univariate analysis, smoking (p = 0.048, OR = 3.15, 95% CI: 1.01–9.93) and low-dose aspirin consumption (p = 0.067, OR = 2.63, 95% CI: 0.95–7.68) were significantly associated with ulcer. According to the multivariable regression model, alcohol consumption (OR = 6.68, 95% CI: 1.29–41.14) and biliary reflux (OR = 6.12, 95% CI: 1.36–38.26) remained significantly associated with increased odds of stump ulcer. Conclusion . Biliary reflux and alcohol consumption, but not Helicobacter pylori infection or gastrotoxic drug, seem to be the most important predictors for ulcer recurrence in patients with gastric surgery for peptic ulcer after more than 15 years.